Electrolytic capacitor

By using specific electrolytes and conductive polymers to form chemical films of appropriate thickness, the problem of the capacity and ESR decrease of hybrid electrolytic capacitors at low chemical voltage ratios is solved, and the stability and self-healing performance of the capacitor are improved.

JP2025015813APending Publication Date: 2025-01-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024202757
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-09-29
Filing Date
2024-11-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Traditional hybrid electrolytic capacitors have difficulty maintaining capacitance and equivalent series resistance (ESR) when reducing the chemical voltage and rated voltage ratio, resulting in a degradation in performance.

Method used

An electrolyte with a specific composition, including lactate compounds, glycol compounds and sulfonic acid compounds of a specific concentration, combines specific acidic and alkaline components, controls the pH value of the electrolyte and the ratio of the chemical voltage to the rated voltage, forms a chemical film of appropriate thickness, and uses conductive polymers to form a solid electrolyte.

Benefits of technology

Effectively maintain the capacitor's capacitance and ESR, improve self-healing performance, and ensure excellent electrical performance can be maintained at low rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015813000001_ABST
    Figure 2025015813000001_ABST
Patent Text Reader

Abstract

To provide an electrolytic capacitor capable of sufficiently maintaining capacitance and ESR.SOLUTION: The disclosed electrolytic capacitor includes a capacitor element and an electrolytic solution. The capacitor element includes an anode body having a chemical conversion film, and a solid electrolyte in contact with the chemical conversion film. The electrolytic solution contains a solvent, a polymer component, and a solute. The solvent contains at least one selected from the group consisting of a lactone compound, a glycol compound, and a sulfone compound. The concentration of the polymer component in the electrolytic solution is 1 mass% or more and 10 mass% or less. The solute contains a predetermined acid component and a predetermined basic component. The concentration of the solute in the electrolytic solution is 20 mass% or more and 40 mass% or less. The concentration of a first acid component in the electrolytic solution is 15 mass% or more. The electrolytic solution has a pH of 4.0 or less. A ratio V / Vw of a formation voltage V applied to the anode body to form the chemical conversion film to a rated voltage Vw of the electrolytic capacitor is 1.5 or more and 1.7 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor comprising a solid electrolyte and an electrolytic solution. [Background technology]

[0002] As a small-sized, large-capacity, low-ESR (equivalent series resistance) capacitor, a so-called hybrid electrolytic capacitor that includes a solid electrolyte and an electrolytic solution is considered to be promising. For example, Patent Document 1 discloses a hybrid electrolytic capacitor in which an oxide film (chemical conversion film) is formed on the surface of an anode body. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2011 / 099261 Brochure Summary of the Invention [Problem to be solved by the invention]

[0004] However, in conventional hybrid electrolytic capacitors, when the ratio of the formation voltage to the rated voltage was lowered, it was not possible to maintain sufficient capacitance and equivalent series resistance (ESR). [Means for solving the problem]

[0005] In view of the above, a first aspect of the present invention comprises: An electrolytic capacitor comprising a capacitor element and an electrolyte, the capacitor element comprises an anode body having a chemical conversion coating and a solid electrolyte in contact with the chemical conversion coating; The electrolyte solution includes a solvent, a polymer component, and a solute, the solvent contains at least one selected from the group consisting of a lactone compound, a glycol compound, and a sulfone compound; The concentration of the polymer component in the electrolyte solution is 1% by mass or more and 10% by mass or less, The solute includes at least one of benzenedicarboxylic acid and its derivative as a first acid component, and at least one of amines and amidines as a base component; The concentration of the solute in the electrolyte is 20% by mass or more and 40% by mass or less, The concentration of the first acid component in the electrolytic solution is 15% by mass or more, The pH of the electrolyte is 4.0 or less; The electrolytic capacitor has a ratio, V / Vw, of a chemical conversion voltage V applied to the anode body for forming the chemical conversion coating to a rated voltage Vw of the electrolytic capacitor, of 1.5 or more and 1.7 or less.

[0006] This specification discloses the following techniques. (Technology 1) An electrolytic capacitor comprising a capacitor element and an electrolyte, the capacitor element comprises an anode body having a chemical conversion coating and a solid electrolyte in contact with the chemical conversion coating; The electrolyte solution includes a solvent and a solute, the solvent contains at least one selected from the group consisting of a lactone compound, a glycol compound, and a sulfone compound; The solute includes at least one of benzenedicarboxylic acid and its derivative as a first acid component, and at least one of amines and amidines as a base component; The concentration of the solute in the electrolyte is 15% by mass or more and 40% by mass or less, an electrolytic capacitor, wherein the ratio of a formation voltage V applied to the anode body for forming the chemical conversion coating to a rated voltage Vw of the electrolytic capacitor: V / Vw is 1.7 or less. (Technology 2) 2. The electrolytic capacitor according to claim 1, wherein the benzenedicarboxylic acid is o-phthalic acid. (Technology 3) An electrolytic capacitor comprising a capacitor element and an electrolyte, the capacitor element comprises an anode body having a chemical conversion coating and a solid electrolyte in contact with the chemical conversion coating; The electrolyte solution includes a solvent and a solute, the solvent contains at least one selected from the group consisting of a lactone compound, a glycol compound, and a sulfone compound; the solute includes, as a first acid component, at least one of a complex compound of an organic acid and an inorganic acid and a derivative thereof, and, as a base component, at least one of an amine and an amidine; The concentration of the solute in the electrolyte is 10% by mass or more and 40% by mass or less, an electrolytic capacitor, wherein the ratio of a formation voltage V applied to the anode body for forming the chemical conversion coating to a rated voltage Vw of the electrolytic capacitor: V / Vw is 1.7 or less. (Technology 4) 4. The electrolytic capacitor according to any one of techniques 1 to 3, wherein the pH of the electrolytic solution is 4.5 or less. (Technology 5) The electrolyte further comprises a polymer component, 5. The electrolytic capacitor according to any one of Techniques 1 to 4, wherein the concentration of the polymer component in the electrolytic solution is 1% by mass or more and 15% by mass or less. (Technology 6) 6. The electrolytic capacitor according to any one of Techniques 1 to 5, wherein the rated voltage Vw is 100 volts or less. (Technology 7) 7. The electrolytic capacitor according to any one of Techniques 1 to 6, wherein the concentration of the base component in the electrolytic solution is 3.5 mass % or more. (Technology 8) The solute further comprises a second acid component other than the first acid component, 8. The electrolytic capacitor according to any one of techniques 1 to 7, wherein the concentration of the second acid component in the electrolytic solution is 3 mass % or more. (Technology 9) The electrolytic capacitor according to any one of Techniques 1 to 8, wherein the lactone compound is γ-butyrolactone. (Technology 10) The electrolytic capacitor according to any one of techniques 1 to 9, wherein the glycol compound is ethylene glycol. (Technology 11) 11. The electrolytic capacitor according to any one of claims 1 to 10, wherein the sulfone compound is sulfolane. Effect of the Invention

[0007] According to the present invention, it is possible to provide a hybrid electrolytic capacitor capable of sufficiently maintaining the capacitance and equivalent series resistance (ESR). [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention. [Diagram 2] 2 is a schematic diagram for explaining the configuration of a capacitor element according to the same embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [First embodiment] The electrolytic capacitor according to the present embodiment includes a capacitor element and an electrolytic solution. The capacitor element includes an anode body having a chemical conversion coating, and a solid electrolyte in contact with the chemical conversion coating.

[0010] In hybrid electrolytic capacitors, the solid electrolyte and the chemical conversion film are in contact with each other. Therefore, in order to reduce leakage current, the chemical conversion voltage V has been set to a high value, about twice the rated voltage Vw of the electrolytic capacitor, to form a sufficiently thick chemical conversion film. Therefore, in hybrid electrolytic capacitors, it has been difficult to increase the capacitance of the electrolytic capacitor or to reduce the size of the electrolytic capacitor by reducing the ratio (V / Vw) of the rated voltage Vw and the chemical conversion voltage V.

[0011] As a result of extensive research, the inventors discovered that by using an electrolyte with a specific composition, it is possible to maintain the capacitance and ESR of a hybrid electrolytic capacitor even when the ratio (V / Vw) of the rated voltage Vw to the formation voltage V is reduced.

[0012] First, a specific solute is used, and its content is set to a specific range. Specifically, a solute containing at least one of benzenedicarboxylic acid and its derivatives as a first acid component and at least one of amine and amidine as a base component is used. The concentration of the solute contained in the electrolyte, that is, the total concentration of the acid component including the first acid component and the base component, is set to 15 mass% or more and less than 40 mass%.

[0013] Second, a specific solvent is used. Specifically, the solvent is at least one selected from the group consisting of γ-butyrolactone, ethylene glycol, and sulfolane.

[0014] By making the electrolyte have the above composition, the first acid component contained in the solute can easily reach the vicinity of defects in the anode body. This improves the self-repairing performance of the chemical conversion coating, and the capacitance and ESR can be maintained. As a result, the ratio of the chemical conversion voltage V to the rated voltage Vw: V / Vw can be set to 1.7 or less.

[0015] In addition, when the polymer component is contained in the electrolytic solution, the concentration of the polymer component is set to 1 mass % or more and 15 mass % or less. This makes it difficult for the migration of the first acid component to be hindered even when the polymer component is contained in the electrolytic solution, thereby obtaining the above-mentioned effect.

[0016] The chemical conversion film is not limited to a film formed by a method (hereinafter, the first method) in which a predetermined chemical conversion voltage is applied to the anode body while it is immersed in an acidic aqueous solution (hereinafter, the chemical conversion solution). For example, the chemical conversion film may be formed by heat treating the anode body while it is immersed in the chemical conversion solution (hereinafter, the second method). When the chemical conversion film is formed by the first method, a chemical conversion film having a thickness T according to the chemical conversion voltage is formed. That is, the chemical conversion voltage is calculated from the thickness T of the chemical conversion film. Even when the chemical conversion film is formed by the second method, the chemical conversion voltage required to form the chemical conversion film by the first method can be calculated from the thickness T. That is, the chemical conversion voltage V includes the voltage applied to the anode body to form a chemical conversion film with the thickness T and the voltage required to form a chemical conversion film with the thickness T.

[0017] The rated voltage Vw is the upper limit voltage defined as a rating, and is the maximum value of the voltage that can be applied between the electrodes of an electrolytic capacitor. [Electrolyte] The electrolyte includes a solvent and a solute.

[0018] The pH of the electrolyte is preferably 4.5 or less. By setting the pH of the electrolyte to 4.5 or less, the dedoping phenomenon of the solid electrolyte is easily suppressed. Therefore, the ESR can be maintained. The pH of the electrolyte is more preferably 4 or less, and particularly preferably 3.8 or less. The pH of the electrolyte is preferably 2 or more.

[0019] The electrolytic solution preferably has an electrical conductivity of 0.01 mS / cm or more and 3 mS / cm or less. In this case, when the ratio of the formation voltage V to the rated voltage Vw: V / Vw is set to 1.7 or less, the self-repairing performance is more likely to be improved. (solvent) The solvent preferably contains at least one selected from the group consisting of γ-butyrolactone (γBL), ethylene glycol (EG) and sulfolane (SL) (hereinafter referred to as the main solvent). As the main solvent, a glycol compound other than EG, a sulfone compound other than SL, or a lactone compound other than γBL may be used. As the glycol compound other than EG, diethylene glycol, triethylene glycol, propylene glycol, etc. can be used. As the sulfone compound other than SL, dimethyl sulfoxide, diethyl sulfoxide, etc. can be used. As the lactone compound other than γBL, γ-valerolactone, etc. can be used. The ratio of the main solvent (for example, the total of γBL, EG and SL) contained in the solvent is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more.

[0020] The solvent may contain a carbonate compound, a monohydric or trihydric or higher alcohol, etc., as a solvent other than the main solvent (hereinafter, a secondary solvent). As the carbonate compound, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), etc. may be used. As the alcohol, for example, glycerin or polyglycerin may be used. These may be used alone or in combination of two or more kinds. (solute) The concentration of the solute is 15% by mass or more and 40% by mass or less, more preferably 20% by mass or more and 40% by mass or less, and particularly preferably 20% by mass or more and 35% by mass or less.

[0021] The concentration of the solute is the sum of the concentration of the acid component and the concentration of the base component. The acid component includes a first acid component and a second acid component other than the first acid component. The base component includes an amine and / or amidine (hereinafter, the first base component) and a second base component other than the first base component.

[0022] The solute contains at least one of benzenedicarboxylic acid and its derivatives as the first acid component. The benzenedicarboxylic acid may be o-phthalic acid, m-phthalic acid, or p-phthalic acid. Examples of the derivatives of benzenedicarboxylic acid include 3-sulfophthalic acid, 3,5-disulfophthalic acid, 4-sulfoisophthalic acid, 2-sulfoterephthalic acid, and 2-methyl-5-sulfoterephthalic acid, each of which has a sulfo group. Among these, o-phthalic acid is preferred.

[0023] The concentration of the first acid component contained in the electrolytic solution is preferably 5% by mass or more, more preferably 15% by mass or more, in terms of ease of dissociation, and is preferably 35% by mass or less, more preferably 30% by mass or less.

[0024] The acid component may include a second acid component other than the first acid component.

[0025] Examples of the organic acid used as the second acid component include polycarboxylic acids, monocarboxylic acids, and polyhydric phenols.

[0026] Examples of polycarboxylic acids include aliphatic polycarboxylic acids ([saturated polycarboxylic acids, such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,6-decanedicarboxylic acid, and 5,6-decanedicarboxylic acid], and [unsaturated polycarboxylic acids, such as maleic acid, fumaric acid, and itanoic acid]), aromatic polycarboxylic acids (such as trimellitic acid and pyromellitic acid), and alicyclic polycarboxylic acids (such as cyclohexane-1,2-dicarboxylic acid and cyclohexene-1,2-dicarboxylic acid).

[0027] Examples of monocarboxylic acids include aliphatic monocarboxylic acids (having 1 to 30 carbon atoms): ([saturated monocarboxylic acids, such as formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, lauric acid, myristic acid, stearic acid, and behenic acid], and [unsaturated monocarboxylic acids, such as acrylic acid, methacrylic acid, and oleic acid]), aromatic monocarboxylic acids: (for example, benzoic acid, cinnamic acid, and naphthoic acid), and oxycarboxylic acids: (for example, salicylic acid, mandelic acid, and resorcylic acid). Of these, preferred are maleic acid, benzoic acid, pyromellitic acid, and resorcylic acid, which have high electrical conductivity and are thermally stable.

[0028] Examples of polyhydric phenols include catechol, resorcinol, hydroquinone, pyrogallol, and phloroglucinone.

[0029] Inorganic acids used as the second acid component include carbon compounds, hydrogen compounds, boron compounds, sulfur compounds, nitrogen compounds, and phosphorus compounds. Representative examples of inorganic acids include phosphoric acid, phosphorous acid, hypophosphorous acid, alkyl phosphate esters, boric acid, boric fluoride, tetrafluoroboric acid, hexafluorophosphoric acid, benzenesulfonic acid, and naphthalenesulfonic acid.

[0030] The second acid component may be a composite compound of an organic acid and an inorganic acid, such as borodiglycolic acid, borodisoxalic acid, or borodisalicylic acid.

[0031] Among these, the second acid component is preferably at least one selected from the group consisting of aromatic polycarboxylic acids, polyhydric phenols and oxycarboxylic acids, in terms of further improving the self-repairing performance.

[0032] The concentration of the second acid component is preferably 3% by mass or more, more preferably 5% by mass or more, and is preferably 25% by mass or less, more preferably 15% by mass or less.

[0033] The solute includes at least one of an amine and an amidine as a first basic component.

[0034] The amine may be a primary amine, a secondary amine, or a tertiary amine. Each amine may be an aliphatic amine, an aromatic amine, or a heterocyclic amine. Among them, a tertiary amine is preferred because it enhances the effect of stabilizing the ESR for a long time.

[0035] Examples of tertiary amines include trialkylamines (trimethylamine, dimethylethylamine, methyldiethylamine, triethylamine, dimethyl n-propylamine, dimethylisopropylamine, methylethyl n-propylamine, methylethylisopropylamine, diethyl n-propylamine, diethylisopropylamine, tri n-propylamine, triisopropylamine, tri n-butylamine, tri t-butylamine, etc.), and phenyl group-containing amines (dimethylphenylamine, methylethylphenylamine, diethylphenylamine, etc.). Among these, trialkylamines such as trimethylamine, dimethylethylamine, methyldiethylamine, and triethylamine are preferred because of their high electrical conductivity.

[0036] As the amidine, a compound having an alkyl-substituted amidine group is preferable in terms of high electrical conductivity. Examples of the compound having an alkyl-substituted amidine group include imidazole compounds, benzimidazole compounds, and alicyclic amidine compounds (pyrimidine compounds, imidazoline compounds). Specifically, 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, 1,2-dimethylimidazolinium, 1,2,4-trimethylimidazoline, 1-methyl-2-ethyl-imidazoline, 1,4-dimethyl-2-ethylimidazoline, 1-methyl-2-heptyl imidazoline, 1-methyl-2-(3'heptyl)imidazoline, 1-methyl-2-dodecyl imidazoline, 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine, 1-methylimidazole, 1-methylbenzimidazole, 1-methyl-1,8-diazabicyclo[5,4,0]undecene-7, 1-methyl- Examples of the imidazolium derivatives include 1,5-diazabicyclo[4,3,0]nonene-5, 1,2,3-trimethylimidazolinium, 1,2,3,4-tetramethylimidazolinium, 1,2-dimethyl-3-ethyl-imidazolinium, 1,3,4-trimethyl-2-ethylimidazolinium, 1,3-dimethyl-2-heptylimidazolinium, 1,3-dimethyl-2-(3'heptyl)imidazolinium, 1,3-dimethyl-2-dodecylimidazolinium, 1,2,3-trimethyl-1,4,5,6-tetrahydropyrimidium, 1,3-dimethylimidazolium, 1-methyl-3-ethylimidazolium, and 1,3-dimethylbenzimidazolium.

[0037] The concentration of the first base component contained in the electrolytic solution is preferably 3.5% by mass or more, more preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less.

[0038] When the electrolyte contains an amine, the concentration is preferably 3.5% by mass or more, more preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less.

[0039] When amidine is contained in the electrolyte, its concentration is preferably 3.5% by mass or more, more preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less.

[0040] The base component may contain a second base component other than the first base component.

[0041] Examples of the second base component include ammonia and quaternary ammonium compounds. The concentration of the second base component is preferably 0.1% by mass or more, more preferably 3% by mass or more. The concentration of the second base component is preferably 20% by mass or less, more preferably 10% by mass or less.

[0042] From the viewpoint of effectively suppressing dedoping of the dopant contained in the conductive polymer, the acid component is preferably in excess of the base component in terms of equivalent ratio. For example, the equivalent ratio of the acid component to the base component is desirably 1 to 30. (polymer component) The electrolytic solution may contain a polymer component for the purposes of suppressing evaporation of the electrolytic solution and improving the withstand voltage.

[0043] The polymer component is not particularly limited. Examples of the polymer component include polyalkylene glycol, derivatives of polyalkylene glycol, and compounds in which at least one hydroxyl group of a polyhydric alcohol is substituted with polyalkylene glycol (including derivatives). Specific examples include polyethylene glycol, polyethylene glycol glyceryl ether, polyethylene glycol diglyceryl ether, polyethylene glycol sorbitol ether, polypropylene glycol, polypropylene glycol glyceryl ether, polypropylene glycol diglyceryl ether, polypropylene glycol sorbitol ether, and polybutylene glycol. These may be used alone or in a mixture of two or more.

[0044] The polyalkylene glycol may be a copolymer (random copolymer, block copolymer, random block copolymer, etc.), such as a copolymer of ethylene glycol and propylene glycol, a copolymer of ethylene glycol and butylene glycol, or a copolymer of propylene glycol and butylene glycol.

[0045] The weight average molecular weight of the polymer component is preferably at least 200. From the viewpoint of solubility in a solvent, the weight average molecular weight of the polymer component is preferably at most 20,000, and more preferably at most 5000.

[0046] The concentration of the polymer component in the electrolyte is preferably 1% by mass or more and 15% by mass or less. If the concentration of the polymer component is in this range, the evaporation of the electrolyte is suppressed and the movement of the first acid component is not hindered. Therefore, the self-repairing performance of the chemical conversion coating is improved. The concentration of the polymer component in the electrolyte is more preferably 1% by mass or more and 10% by mass or less. (solid electrolyte) The solid electrolyte includes, for example, a manganese compound and a conductive polymer. As the conductive polymer, for example, polypyrrole, polythiophene, polyaniline, and derivatives thereof can be used. The solid electrolyte includes a dopant. More specifically, the solid electrolyte can include poly(3,4-ethylenedioxythiophene) (PEDOT) as the conductive polymer and polystyrene sulfonic acid (PSS) as the dopant.

[0047] The solid electrolyte may be formed by applying a solution containing a monomer and a dopant to the chemical conversion coating and then performing chemical polymerization or electrolytic polymerization in situ. However, it is preferable to form the solid electrolyte by applying a conductive polymer to the chemical conversion coating, since excellent voltage resistance characteristics can be expected. That is, the solid electrolyte is preferably formed by impregnating the chemical conversion coating with a polymer dispersion containing a liquid component, a conductive polymer dispersed in the liquid component, and a dopant, and then volatilizing the liquid component.

[0048] The concentration of the conductive polymer contained in the polymer dispersion is preferably 0.5 to 10 mass %. The conductive polymer preferably has an average particle size D50 of, for example, 0.01 to 0.5 μm. Here, the average particle size D50 is the median diameter in the volume particle size distribution determined by a particle size distribution measuring device using a dynamic light scattering method. (Formation voltage V and rated voltage Vw) The ratio V / Vw of the chemical conversion voltage V applied to the anode body to form a chemical conversion coating having a thickness T to the rated voltage Vw of the electrolytic capacitor is 1.7 or less. V / Vw may be 1.6 or less. From the viewpoint of suppressing an increase in leakage current, V / Vw is preferably 1.4 or more, and more preferably 1.5 or more.

[0049] The formation voltage V is not particularly limited, and may be set appropriately according to the rated voltage Vw so that V / Vw is 1.7 or less. The thickness T of the chemical film increases in proportion to the formation voltage V. For example, when the formation voltage V is 17 volts, the thickness T of the chemical film is 24 nm. When the formation voltage V is 170 volts, the thickness T of the chemical film is 238 nm. In other words, when the thickness T of the chemical film is 238 nm, the formation voltage V applied to or required for the anode body is 170 volts.

[0050] The rated voltage Vw is not particularly limited, but the effects of the present invention are particularly likely to be exhibited when the rated voltage Vw is 100 V or less (i.e., the thickness T of the chemical conversion coating is 238 nm or less). In particular, the effects of the present invention are even more pronounced when the rated voltage Vw is 70 V or less, at which the chemical conversion coating becomes even thinner.

[0051] The present invention will be described in more detail below based on the embodiments, however, the present invention is not limited to the following embodiments.

[0052] FIG. 1 is a schematic cross-sectional view of the electrolytic capacitor according to this embodiment, and FIG. 2 is a schematic exploded view of a portion of a capacitor element of the electrolytic capacitor.

[0053] The electrolytic capacitor includes, for example, a capacitor element 10, a bottomed case 11 that houses the capacitor element 10, a sealing member 12 that closes the opening of the bottomed case 11, a seat plate 13 that covers the sealing member 12, lead wires 14A, 14B that are led out from the sealing member 12 and pass through the seat plate 13, lead tabs 15A, 15B that connect the lead wires to electrodes of the capacitor element 10, and an electrolyte (not shown). The vicinity of the open end of the bottomed case 11 is drawn inward, and the open end is curled so as to be crimped to the sealing member 12.

[0054] Capacitor element 10 is produced from a wound body as shown in Fig. 2. The wound body includes an anode body 21 connected to lead tab 15A, a cathode body 22 connected to lead tab 15B, and a separator 23. The wound body is a semi-finished product in which no solid electrolyte is formed between anode body 21 and cathode body 22.

[0055] Anode body 21 and cathode body 22 are wound with separator 23 interposed therebetween. The outermost periphery of the wound body is fixed with stop tape 24. Note that Fig. 2 shows a partially unfolded state of the wound body prior to the outermost periphery being fixed.

[0056] Anode body 21 comprises a metal foil whose surface has been roughened to have projections and recesses, and a chemical conversion coating is formed on the metal foil having projections and recesses. A solid electrolyte is attached to at least a portion of the surface of the chemical conversion coating. The solid electrolyte may cover at least a portion of the surface of cathode body 22 and / or the surface of separator 23. Capacitor element 10 on which the solid electrolyte is formed is accommodated in bottomed case 11 together with an electrolytic solution. <Manufacturing method of electrolytic capacitors> Hereinafter, an example of a method for manufacturing the electrolytic capacitor according to this embodiment will be described step by step. (i) A step of preparing an anode body 21 having a chemical conversion coating First, prepare a metal foil as the raw material of the anode body 21. Although the type of metal is not particularly limited, it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal, because it is easy to form a chemical conversion coating.

[0057] Next, the surface of the metal foil is roughened. By roughening, a plurality of projections and recesses are formed on the surface of the metal foil. The roughening is preferably performed by etching the metal foil. The etching may be performed by, for example, DC electrolysis or AC electrolysis.

[0058] Next, a chemical conversion coating having a thickness T is formed on the roughened surface of the metal foil. The method of formation is not particularly limited, but the metal foil can be subjected to a chemical conversion treatment. In the chemical conversion treatment, for example, the metal foil is immersed in a chemical conversion solution such as an ammonium adipate solution and heat-treated. Alternatively, the metal foil may be immersed in the chemical conversion solution and a voltage may be applied.

[0059] Usually, from the viewpoint of mass production, a large-sized foil (metal foil) of a valve metal or the like is subjected to a surface roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut to a desired size to prepare the anode body 21. (ii) A step of preparing the cathode body 22 A metal foil can be used for the cathode body 22, as with the anode body 21. The type of metal is not particularly limited, but it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal. If necessary, the surface of the cathode body 22 may be roughened.

[0060] Moreover, a layer containing titanium or carbon may be formed on the surface of the cathode body 22 . (iii) Preparation of the roll Next, a wound body as shown in Fig. 2 is produced using anode body 21, cathode body 22, and separator 23. The end of cathode body 22 located in the outermost layer is fixed with stop tape 24. When anode body 21 is prepared by cutting a large metal foil, the wound body may be further subjected to a chemical conversion treatment in order to provide a chemical conversion coating on the cut surface of anode body 21. As separator 23, for example, a nonwoven fabric mainly composed of cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like can be used. (iv) Step of forming capacitor element 10 Next, a solid electrolyte is applied to the surface of the chemical conversion coating included in the wound body to produce the capacitor element 10. When the solid electrolyte contains a conductive polymer, a conductive polymer synthesized in situ by chemical polymerization or electrolytic polymerization using a polymerization liquid may be applied to the chemical conversion coating. The polymerization liquid is a solution containing a monomer or oligomer, a dopant, etc. In the case of chemical polymerization, an oxidizing agent is added to the polymerization liquid. Alternatively, a conductive polymer synthesized in advance may be applied to the chemical conversion coating. Examples of the monomer or oligomer include pyrrole, aniline, thiophene, and derivatives thereof.

[0061] As the conductive polymer synthesized in advance, it is preferable to use a polymer dispersion. The polymer dispersion includes a liquid component, a conductive polymer dispersed in the liquid component, and a dopant. As a method for applying the polymer dispersion to the surface of the chemical conversion coating, for example, a method of impregnating a rolled body with the polymer dispersion and drying it is simple and preferable. The polymer dispersion preferably includes PEDOT as the conductive polymer and PSS as the dopant.

[0062] The step of applying the polymer dispersion to the surface of the chemical conversion coating and the step of drying the roll may be repeated two or more times. By performing these steps multiple times, the coverage rate of the solid electrolyte with respect to the chemical conversion coating can be increased. (v) A step of impregnating the capacitor element 10 with an electrolyte Next, the electrolyte is impregnated into capacitor element 10. The method for impregnating capacitor element 10 with the electrolyte is not particularly limited. (vi) Encapsulating the capacitor element Next, capacitor element 10 is housed in bottomed case 11. Bottomed case 11 can be made of metals such as aluminum, stainless steel, copper, iron, brass, or alloys thereof. Thereafter, a horizontal drawing process is performed near the open end of bottomed case 11, and the open end is curled by crimping it to sealing member 12. Then, seat plate 13 is placed on the curled portion, completing an electrolytic capacitor as shown in FIG. 1. Then, an aging process may be performed while applying a rated voltage.

[0063] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, for example, chip-type electrolytic capacitors that use a metal sintered body as an anode body, and stacked-type electrolytic capacitors that use a metal plate as an anode body. [Second embodiment] The electrolytic capacitor according to the second embodiment of the present invention will be described. The electrolytic capacitor according to the second embodiment has the same configuration as the first embodiment, except that the first acid component contains at least one of a composite compound of an organic acid and an inorganic acid and its derivatives, and therefore the description of the overlapping contents will be omitted.

[0064] In this embodiment, the complex compound as the first acid component preferably contains one or more selected from the group consisting of borodisalicylic acid, borodiglycolic acid, and borodisalic acid.

[0065] The concentration of the solute contained in the electrolytic solution, that is, the total concentration of the acid component including the first acid component and the base component, is set to 10% by mass or more and less than 40% by mass. The concentration of the solute is more preferably 15% by mass or more and 35% by mass or less, and particularly preferably 20% by mass or more and 35% by mass or less. When a composite compound is used as the first acid component, since the degree of dissociation in the electrolytic solution is high, even if the concentration of the solute is 10% by mass or more, the first acid component can easily reach the vicinity of defects in the anode body as in the first embodiment, and the self-repair performance of the chemical conversion coating can be improved. In addition, since the composite compound has excellent heat resistance, the electrolytic solution containing the composite compound easily maintains pH, and dedoping from the conductive polymer can be suppressed, so that the ESR can be maintained. [Example] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Example 1 A wound-type electrolytic capacitor (Φ10 mm × L (length) 10 mm) with a rated voltage Vw of 25 volts and a rated capacitance of 33 μF was fabricated in the following manner. (Preparation of anode body) An aluminum foil having a thickness of 100 μm was etched to roughen the surface of the aluminum foil. The roughened surface of the aluminum foil was chemically treated to form a chemical coating. The chemical treatment was performed by immersing the aluminum foil in an ammonium adipate solution and applying a voltage of 40 volts to the aluminum foil. The aluminum foil was then cut to 6 mm × 120 mm to prepare an anode body. V / Vw was set to 1.6. The thickness T of the chemical coating was 55 nm. (Preparation of the cathode body) An aluminum foil having a thickness of 50 μm was subjected to an etching treatment to roughen the surface of the aluminum foil, and then cut into a size of 6 mm×120 mm to prepare a cathode body. (Making of the roll) An anode lead tab and a cathode lead tab were connected to the anode body and the cathode body, and the anode body and the cathode body were wound with the lead tabs interposed between them. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. The obtained wound body was again subjected to chemical conversion, and a chemical conversion coating was formed on the cut ends of the anode body. The ends of the outer surface of the wound body were fixed with a stop tape. (Preparation of polymer dispersion) 3,4-Ethylenedioxythiophene and polystyrene sulfonic acid (PSS, weight average molecular weight 100,000) were dissolved in ion-exchanged water to prepare a mixed solution. Iron (III) sulfate (oxidant) was added while stirring the mixed solution to carry out a polymerization reaction. The reaction solution was then dialyzed to remove unreacted monomers and the oxidant, and a polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of PSS (PEDOT / PSS) was obtained. (Formation of solid electrolyte) The wound body was immersed in the polymer dispersion for 5 minutes in a reduced pressure atmosphere (40 kPa), and then the wound body was removed from the polymer dispersion. The wound body impregnated with the polymer dispersion was then dried in a drying oven at 150°C for 20 minutes to form a solid electrolyte that covered at least a part of the chemical conversion coating. (Electrolyte Impregnation) γ-Butyrolactone (γBL) and sulfolane were prepared as a solvent. o-Phthalic acid as the first acid component and triethylamine as the first base component were dissolved in this solvent at a total concentration of 19 mass% and an equivalent ratio (initial equivalent ratio) of 1. PEG (weight average molecular weight 300) was dissolved in the solution obtained above at a concentration of 10 mass%. Finally, o-phthalic acid was added at 12 mass% and pyrogallol was added at 3 mass% to adjust the pH of the electrolyte to 3.5 to prepare an electrolyte. A capacitor element was immersed in the electrolyte for 5 minutes in a reduced pressure atmosphere (40 kPa). The concentration of each component is a ratio when the mass of the obtained electrolyte is 100%. The concentration of the acid component was 28.2 mass%, and the concentration of the base component was 5.8 mass%. (Sealing of capacitor elements) The capacitor element impregnated with the electrolyte was sealed to complete the electrolytic capacitor (A1) as shown in Figure 1. Thereafter, aging was performed at 95°C for 90 minutes while applying the rated voltage Vw. <Evaluation> The capacitance and ESR of the capacitor A1 were measured after aging and after 2500 hours. The value after 2500 hours was divided by the value after aging to calculate the rate of change. The results are shown in Table 1. Examples 2 to 5 Electrolytic capacitors A2 to A5 were produced and evaluated in the same manner as in Example 1, except that the concentration of PEG was changed as shown in Table 1. The results are shown in Table 1. Comparative Example 1 Electrolytic capacitor B1 was produced and evaluated in the same manner as in Example 1, except that the initial equivalent ratio of the first acid component and the first base component was not changed, the initial solute concentration was 10 mass%, the concentration of additional o-phthalic acid was 4 mass%, and pyrogallol was not added (the total concentration of solutes was 14 mass%). The results are shown in Table 1. The concentration of the acid component was 10.9 mass%, and the concentration of the base component was 3.1 mass%. Comparative Example 2 Except for setting the formation voltage V to 45 volts and V / Vw to 1.8, electrolytic capacitor B2 was produced and evaluated in the same manner as in Comparative Example 1. The results are shown in Table 1.

[0066] [Table 1]

[0067] Example 6 Except for adding 4% by mass of pyromellitic acid and 5% by mass of pyrogallol instead of the additional o-phthalic acid (12% by mass) and changing the concentration of PEG to 15% by mass, an electrolytic capacitor A6 was produced and evaluated in the same manner as in Example 1. The results are shown in Table 2. Example 7 An electrolytic capacitor A7 was produced and evaluated in the same manner as in Example 1, except that the initial equivalent ratio of the first acid component and the first base component was not changed, the initial solute concentration was set to 12 mass%, and 3 mass% of pyromellitic acid was added instead of pyrogallol. The results are shown in Table 2. Example 8 Except for the fact that the initial equivalent ratio of the first acid component and the first base component was not changed, the initial solute concentration was 10 mass%, and pyrogallol was not added, an electrolytic capacitor A8 was produced and evaluated in the same manner as in Example 1. The results are shown in Table 2. Example 9 Except for changing the concentration of the additional o-phthalic acid to 6 mass %, an electrolytic capacitor A9 was produced and evaluated in the same manner as in Example 1. The results are shown in Table 2. Example 10 An electrolytic capacitor A10 was produced and evaluated in the same manner as in Example 1, except that the initial equivalent ratio of the first acid component and the first base component was not changed, the initial solute concentration was 25 mass%, the concentration of the additional o-phthalic acid was 10 mass%, and the concentration of pyrogallol was 5 mass%. The results are shown in Table 2.

[0068] [Table 2]

[0069] Example 11 Except for the fact that the formation voltage V was 35 volts, the V / Vw was 1.4, and pyrogallol was not added, the electrolytic capacitor A11 was produced and evaluated in the same manner as in Example 1. The results are shown in Table 3. Comparative Example 3 Except for setting the formation voltage V to 35 volts and V / Vw to 1.4, electrolytic capacitor B3 was produced and evaluated in the same manner as in Comparative Example 1. The results are shown in Table 3.

[0070] [Table 3]

[0071] Example 12 Electrolytic capacitor A12 was produced and evaluated in the same manner as in Example 1, except that 1,2,3,4-tetramethylimidazolinium, an amidine, was used instead of triethylamine as the first base component, and the initial equivalent ratio of the first acid component to the first base component was not changed and the initial solute concentration was 14 mass%. The results are shown in Table 4. The concentration of the acid component was 22.2 mass%, and the concentration of the base component was 6.8 mass%. Example 13 Except for not adding PEG, electrolytic capacitor A13 was produced and evaluated in the same manner as in Example 12. The results are shown in Table 4.

[0072] [Table 4] [Industrial Applicability]

[0073] The present invention can be applied to a hybrid electrolytic capacitor having a solid electrolyte and an electrolytic solution. [Explanation of symbols]

[0074] 10: capacitor element, 11: bottomed case, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead tabs, 21: anode body, 22: cathode body, 23: separator, 24: winding stop tape

Claims

[Claim 1] An electrolytic capacitor comprising a capacitor element and an electrolyte, the capacitor element comprises an anode body having a chemical conversion coating and a solid electrolyte in contact with the chemical conversion coating; The electrolyte solution includes a solvent, a polymer component, and a solute, the solvent contains at least one selected from the group consisting of a lactone compound, a glycol compound, and a sulfone compound; The concentration of the polymer component in the electrolyte solution is 1% by mass or more and 10% by mass or less, The solute includes at least one of benzenedicarboxylic acid and its derivative as a first acid component, and at least one of amines and amidines as a base component; The concentration of the solute in the electrolyte solution is 20% by mass or more and 40% by mass or less, The concentration of the first acid component in the electrolytic solution is 15% by mass or more, The pH of the electrolyte is 4.0 or less; an electrolytic capacitor, wherein a ratio of a chemical conversion voltage V applied to the anode body for forming the chemical conversion coating to a rated voltage Vw of the electrolytic capacitor: V / Vw is 1.5 or more and 1.7 or less.

Citation Information

Patent Citations

  • Electrolytic capacitor

    WO2011099261A1